PELATIHAN DASAR AUTOCAD UNTUK PELAJAR DAN PEMUDA DI DESA JEJALEN JAYA - Mokhamad Iskandar Zulkarnaen; Sri Nuryati; Elma Yulius (An-Nizam, 2022)
CAD (Computer Aided Design) is an automation software that uses various design tools with computers to help engineers, architects and other professionals with planning needs. CAD allows a person to prepare drawings quickly and accurately, and makes it easier to visualize his ideas and ideas well. While AutoCAD is one of the most popular CAD software developed by Autodesk for 2-dimensional or 3-dimensional drawing. Many high school students are not familiar with AutoCAD because there are no subjects for this program at school. Therefore, they are new to AutoCAD when they are in college when they take a major related to drawing, planning or designing. This AutoCAD training is very useful in planning or designing something starting from goods or buildings. The stages in this training are the first introduction to AutoCAD software, the second 2-dimensional drawing exercise. After participating in this training, participants are expected to be able to recognize and master the AutoCAD program well. So that it can be applied in design planning if one day there are participants who are interested or involved in a job that requires designing skills.